Evolution of the Kurikulum Merdeka: Evaluation and recommendations for the future curriculum - Adam Mahfud; Eka Setya Budi (Himpunan Pengembang Kurikulum Indonesia, 2025)
The Kurikulum Merdeka was developed as an effort in the Indonesian education system aimed at providing more flexibility in learning, encouraging differentiation in teaching, and strengthening the character of students. However, its implementation faces various challenges, especially in teacher administration, student competency assessment, and subject integration. This study aims to evaluate the evolution of the Kurikulum Merdeka, identify the main challenges in its implementation, and provide recommendations for future curriculum development. This study employs a qualitative approach, utilizing a literature review method to analyze various sources, including education policies, academic journals, research reports, and news articles related to curriculum implementation. The results of the study indicate that the high administrative burden hinders the effectiveness of teaching, the elimination of the National Examination makes it challenging to objectively measure student competencies, and the merging of Natural Sciences and Social Sciences subjects creates obstacles to a deeper understanding of concepts. As recommendations, this study proposes several strategic steps, including simplifying teacher administration through the use of technology, implementing deep learning-based assessments to measure student competencies more accurately, and re-separating Natural Sciences and Social Sciences subjects to improve learning effectiveness. Abstrak Kurikulum Merdeka dikembangkan sebagai upaya dalam sistem pendidikan Indonesia yang bertujuan untuk memberikan lebih banyak fleksibilitas dalam pembelajaran, mendorong diferensiasi pengajaran, serta memperkuat karakter peserta didik. Namun, implementasinya menghadapi berbagai tantangan, terutama dalam administrasi guru, asesmen kompetensi peserta didik, dan integrasi mata pelajaran. Studi ini bertujuan untuk mengevaluasi evolusi Kurikulum Merdeka, mengidentifikasi tantangan utama dalam penerapannya, serta memberikan rekomendasi bagi pengembangan kurikulum di masa depan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur, menganalisis berbagai sumber seperti kebijakan pendidikan, jurnal akademik, laporan penelitian, serta berita mengenai implementasi kurikulum. Hasil penelitian menunjukkan bahwa beban administratif yang tinggi mengurangi efektivitas pengajaran, penghapusan Ujian Nasional menyebabkan kesulitan dalam mengukur kompetensi peserta didik secara objektif, dan penggabungan mata pelajaran Ilmu Pengetahuan Alam dan Ilmu Pengetahuan Sosial menimbulkan hambatan dalam pemahaman konsep yang lebih mendalam. Sebagai rekomendasi, studi ini mengusulkan beberapa langkah strategis, antara lain penyederhanaan administrasi guru melalui pemanfaatan teknologi, penerapan asesmen berbasis deep learning untuk mengukur kompetensi peserta didik secara lebih akurat, serta pemisahan kembali mata pelajaran Ilmu Pengetahuan Alam dan Ilmu Pengetahuan Sosial guna meningkatkan efektivitas pembelajaran. Kata Kunci: Kurikulum Merdeka; pembelajaran mendalam; pendidikan